2023
DOI: 10.1038/s41598-023-40084-x
|View full text |Cite|
|
Sign up to set email alerts
|

Green innovation efficiency and multiple paths of urban sustainable development in China: multi-configuration analysis based on urban innovation ecosystem

Jinguang Guo,
Yu Fu,
Xuefu Sun

Abstract: Enhancing the effectiveness of urban green innovation is a powerful strategy for advancing urban sustainability. A strong urban innovation ecosystem is a crucial building block for advancing urban green innovation’s effectiveness. We use the fsQCA method to investigate the pathways and models of innovation ecosystems to promote the green innovation efficiency of cities from a histological perspective, using 71 innovative cities in China as cases. This method is based on the DEA-SBM model to measure the green i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…And the results of this paper, which analyzed the regional differences of GIE on the city level, also confirms this. Meanwhile, we found that GIE in the Eastern region, which is better supported by open economies and innovation [42], was continuously improving at the fastest speed among the three regions. This is inconsistent with Zhao's research [11], which pointed out that GIE in the Eastern region decreased slightly based on provincial analysis.…”
Section: Discussionmentioning
confidence: 91%
“…And the results of this paper, which analyzed the regional differences of GIE on the city level, also confirms this. Meanwhile, we found that GIE in the Eastern region, which is better supported by open economies and innovation [42], was continuously improving at the fastest speed among the three regions. This is inconsistent with Zhao's research [11], which pointed out that GIE in the Eastern region decreased slightly based on provincial analysis.…”
Section: Discussionmentioning
confidence: 91%
“…By listing several control variables, other factors that may affect the innovation capability of a city can be controlled to ensure the accuracy of the analysis. The following is an explanation of each control variable and an explanation of the reasonableness of the selection: (i) Level of economic development (rpgdp) [25,26]: The per capita gross national product (GNP) is an important index for measuring the economic prosperity of a region or city. It reflects the average economic value created by each resident and is a representative indicator of the overall economic level of a city or region.…”
Section: Control Variablesmentioning
confidence: 99%
“…The flow of innovation factors will be accelerated further, leading to a rise in innovation outputs and a further expansion of innovation inputs as there are more people and resource inputs. In accordance with Guo et al's methodology, this article chooses human, material, and capital inputs as the secondary indicators of innovation inputs[73][74][75]. 2.…”
mentioning
confidence: 99%